2019
DOI: 10.1515/jisys-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Segmentation of Lung Parenchyma Using Break and Repair Strategy

Abstract: The traditional segmentation methods available for pulmonary parenchyma are not accurate because most of the methods exclude nodules or tumors adhering to the lung pleural wall as fat. In this paper, several techniques are exhaustively used in different phases, including two-dimensional (2D) optimal threshold selection and 2D reconstruction for lung parenchyma segmentation. Then, lung parenchyma boundaries are repaired using improved chain code and Bresenham pixel interconnection. The proposed method of segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The research result in the detection of most of the features inclusive of nerves, exudates and optic disk and greater important with accurately using of image operating algorithms [5]. The research revealed the use of back-propagation neural network, the Bayesian neural network, the probabilistic neural community and the aid vector device, all applied to develop class fashions for finding Ischemic Heart Disease (IHD) sufferers [6,7]. Their studies made use of a guide vector device with Gaussian radial basis characteristic as a classifier.…”
Section: Literature Surveymentioning
confidence: 99%
“…The research result in the detection of most of the features inclusive of nerves, exudates and optic disk and greater important with accurately using of image operating algorithms [5]. The research revealed the use of back-propagation neural network, the Bayesian neural network, the probabilistic neural community and the aid vector device, all applied to develop class fashions for finding Ischemic Heart Disease (IHD) sufferers [6,7]. Their studies made use of a guide vector device with Gaussian radial basis characteristic as a classifier.…”
Section: Literature Surveymentioning
confidence: 99%
“…In addition, the incidence of pneumonia is high in working-age patients and is also the leading infectious disease in that population [3]. Features of pulmonary lesions, such as their shape, margin, and orientation, are fundamental for predicting treatment outcomes as well as in distinguishing benign and malignant lesions [5][6][7]. Thus, precise and reliable segmentation is required for quantification in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Segmentation on biomedical images can be classified as conventional non-DNN approaches and DNN approaches. Conventional methods usually design artificial features (such as oriented gradients [14,15], Haar features [14,15], curvature [16,17], and Haralick texture features [18]) on images and then construct various segmentation models (such as graph models [6,19] and shape models [20][21][22][23]) to differentiate abnormal regions. For example, Soliman et al [23] integrated two visual appearances of lungs to form their shape model for lung segmentation on CT chest images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches include model‐based method [11], the energy minimisation method [12], the shape analysis strategies [13–15], and active contour models [16, 17]. Zhang et al [18] proposed a novel gradient vector flow over manifold (GVFOM) method for an object segmentation.…”
Section: Introductionmentioning
confidence: 99%